1988
DOI: 10.1152/jn.1988.59.2.299
|View full text |Cite
|
Sign up to set email alerts
|

Single-unit analysis of the human ventral thalamic nuclear group: somatosensory responses

Abstract: 1. We have studied the functional and somatotopic properties of 531 single mechanoreceptive thalamic neurons in humans undergoing stereotactic surgery for the control of movement disorders and pain. The majority of these somatosensory cells had small receptive fields (RFs) and were activated in a reproducible manner by mechanical stimuli applied to the skin or deep tissues. These neurons, which we termed "lemniscal," could be further classified into those responding to stimulation of cutaneous (76% of lemnisca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
112
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(125 citation statements)
references
References 0 publications
11
112
0
2
Order By: Relevance
“…A guiding principle is the established somatotopic organization of the somaesthetic thalamic and PAG regions. Human microelectrode studies reveal a mediolateral somatotopy in the contralateral ventroposterior thalamus, the head of the homunculus being medial and the feet lateral [83]. Subjective observation of a rostrocaudally inverted sensory homunculus in contralateral PAG has been confirmed objectively by our human macroelectrode recordings of somatosensory evoked potentials [84,85].…”
Section: Anatomysupporting
confidence: 68%
“…A guiding principle is the established somatotopic organization of the somaesthetic thalamic and PAG regions. Human microelectrode studies reveal a mediolateral somatotopy in the contralateral ventroposterior thalamus, the head of the homunculus being medial and the feet lateral [83]. Subjective observation of a rostrocaudally inverted sensory homunculus in contralateral PAG has been confirmed objectively by our human macroelectrode recordings of somatosensory evoked potentials [84,85].…”
Section: Anatomysupporting
confidence: 68%
“…One possibility is that tremor-related activity is generated in a globally synchronous manner by the motor thalamus (8,10) and is transmitted to the globus pallidus. The plausibility of a thalamic origin is supported by the presence of tremorrelated activity in the motor thalamus (4,(12)(13)(14). This activity has been proposed to result from a low-threshold calcium current in thalamocortical neurons that can sustain an oscillation in membrane potential and can be triggered by hyperpolarizing input from the globus pallidus (8,10).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence support this hypothesis. First, tremor-related neural activity has been observed in the motor thalamus (4,(12)(13)(14) and the posteroventral globus pallidus (11). Second, tremor is effectively ameliorated by making a lesion in the motor thalamus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that a larger lesion in Vim is required to alleviate tremor that is of a lower frequency and involves proximal body parts 27. One reason for this may be found in the somatotopic organization in Vim, which is similar in humans28 and nonhuman primates;29 the leg is represented in the most rostral and lateral regions, the orofacial structures in the most caudal and medial locations, and the fingers, forearm and proximal arm are located in between from medial to lateral and from caudal to rostral directions. Therefore, amelioration of tremor in SCA, which involves both the distal and proximal arm would need to include a larger area of the Vim as compared with that of tremor in ET, which may involve relatively more distal portions of the arm.…”
Section: Discussionmentioning
confidence: 99%